The bidirectional regulatory network between ATF4 and lncRNAs in systemic diseases - Wu, Dongdong; Huang, Mei; Ma, Changning; Xu, Xuetong; Wu, Tianhui; Zhang, Miao (Frontiers in Oncology, 2025)
Long non-coding RNAs (lncRNAs) are pivotal regulators of gene expression across multiple biological contexts, including stress responses and cellular adaptation. Activating transcription factor 4 (ATF4) is a key transcriptional effector of the integrated stress response (ISR), modulating genes involved in redox balance, amino acid metabolism, autophagy, and apoptosis. Emerging evidence has uncovered complex interactions between ATF4 and lncRNAs in systemic diseases, where lncRNAs can act as either downstream targets or upstream modulators of ATF4 signaling. This bidirectional crosstalk influences critical processes such as tumor progression, metabolic reprogramming, immune evasion, and skeletal homeostasis. In this review, we comprehensively summarize the regulatory roles of ATF4–lncRNA interactions in four major physiological systems: digestive, respiratory, immune, and skeletal. Furthermore, we highlight the therapeutic potential of selectively targeting these lncRNAs to modulate ATF4-mediated stress responses in a disease- and context-dependent manner. Our insights provide a conceptual framework and translational perspective for future research and precision therapies targeting the ATF4–lncRNA regulatory axis.